2010
DOI: 10.1017/s1751731110000145
|View full text |Cite
|
Sign up to set email alerts
|

Naringin dietary supplementation at 0.15% rates does not provide protection against sub-clinical acidosis and does not affect the responses of fattening lambs to road transportation

Abstract: Forty Assaf fattening lambs (initial age 13 to 15 weeks) offered a diet of barley straw and a commercial concentrate were used to assess the effect of naringin (a type of citrus flavonoid with proven antioxidant, antimicrobial and anti-inflammatory properties in monogastric animals) at a dose of 1.5 g/kg per dry matteron plasma lipid peroxidation thiobarbituric acid reactive substances (TBARS), immune response, ruminal bacterial community and protection provided by the ruminal wall against subclinical acidosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…In addition, Gnanamani et al (2008) suggested a chelating effect of naringenin (the aglycone fraction of naringin) on the ferrous ion needed to form the central core of both haemoglobin and myoglobin. Both reports are in agreement with the lower red blood cell counts detected in the NARINGIN group when compared with the CONTROL group (Ló pez-Campos et al, 2010). Regarding the effects on meat colour, only numerical TBARS 5 thiobarbituric acid-reactive substances procedure; MDA5malondialde-hyde; 7a-HC 5 7a-hydroxycholesterol; 7b-HC 5 7b-hydroxycholesterol; a-CE 5 5,6a-epoxycholesterol; b-CE 5 5,6b-epoxycholesterol; CT 5 cholestanetriol; 25-HC 5 25-hydroxycholesterol; 7-KC 5 7-ketocholesterol.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, Gnanamani et al (2008) suggested a chelating effect of naringenin (the aglycone fraction of naringin) on the ferrous ion needed to form the central core of both haemoglobin and myoglobin. Both reports are in agreement with the lower red blood cell counts detected in the NARINGIN group when compared with the CONTROL group (Ló pez-Campos et al, 2010). Regarding the effects on meat colour, only numerical TBARS 5 thiobarbituric acid-reactive substances procedure; MDA5malondialde-hyde; 7a-HC 5 7a-hydroxycholesterol; 7b-HC 5 7b-hydroxycholesterol; a-CE 5 5,6a-epoxycholesterol; b-CE 5 5,6b-epoxycholesterol; CT 5 cholestanetriol; 25-HC 5 25-hydroxycholesterol; 7-KC 5 7-ketocholesterol.…”
Section: Discussionsupporting
confidence: 89%
“…Previous reports on flavonoids have shown that degradation products including NA may be metabolized to volatile fatty acids and thus modify microbial diversity in the rumen, enhancing the molar proportion of propionate while decreasing the acetate:propionate ratio [19,61]. Balcells et al [62] fed a concentrate, barley straw, and supplemented Fleckvieh heifers with Bioflavex (containing NA) (0.3 g/kg DM) and recorded an increase in the molar proportion of propionate.…”
Section: Rumen Fermentation Parametersmentioning
confidence: 99%
“…Naringin is responsible for the distinctive sour flavor and bitter taste of grapefruits and other citrus fruits. It possesses a wide range of biological effects such as antioxidant, anti-inflammatory (in vitro and in vivo), immune response, antiapoptotic, hepatoprotective, and cardioprotective effects, along with improving gut health and having a beneficial effect in certain metabolic diseases [19,20]. Flavonoids have antimicrobial properties that may participate in the reduction of methanogenic archaea, replace chemical compounds and, at the same time, improve animal health, feed efficiency, and productivity [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…β-sitosterol (BSS), one phytosterol (plantsterol), has been proven to relieve inflammatory response and control ruminal fermentation after high-grain diets consumption (Xia et al, 2020). Additional, Naringin, a type of citrus flavonoid with proven antioxidant properties, reduces the discomfort that might be associated with damage to the ruminal wall in cases of subclinical acidosis (Lopez-Campos et al, 2010).…”
Section: Flavonoids Essential Oils and Antioxidantsmentioning
confidence: 99%